Levothyroxine Treatment and Cardiovascular Outcomes in Older People With Subclinical Hypothyroidism: Pooled Individual Results of Two Randomised Controlled Trials - Zijlstra, Laurien E.; Jukema, J. Wouter; Westendorp, Rudi G. J.; Du Puy, Robert S.; Poortvliet, Rosalinde K. E.; Kearney, Patricia M.; O’Keeffe, Linda; Dekkers, Olaf M.; Blum, Manuel R.; Rodondi, Nicolas; Collet, Tinh-Hai; Quinn, Terence J.; et al. (Frontiers in Endocrinology, 2021)
Background The cardiovascular effects of treating older adults with subclinical hypothyroidism (SCH) are uncertain. Although concerns have been raised regarding a potential increase in cardiovascular side effects from thyroid hormone replacement, undertreatment may also increase the risk of cardiovascular events, especially for patients with cardiovascular disease (CVD). Objective To determine the effects of levothyroxine treatment on cardiovascular outcomes in older adults with SCH. Methods Combined data of two parallel randomised double-blind placebo-controlled trials TRUST (Thyroid hormone Replacement for Untreated older adults with Subclinical hypothyroidism – a randomised placebo controlled Trial) and IEMO80+ (the Institute for Evidence-Based Medicine in Old Age 80-plus thyroid trial) were analysed as one-stage individual participant data. Participants aged ≥65 years for TRUST (n=737) and ≥80 years for IEMO80+ (n=105) with SCH, defined by elevated TSH with fT4 within the reference range, were included. Participants were randomly assigned to receive placebo or levothyroxine, with titration of the dose until TSH level was within the reference range. Cardiovascular events and cardiovascular side effects of overtreatment (new-onset atrial fibrillation and heart failure) were investigated, including stratified analyses according to CVD history and age. Results The median [IQR] age was 75.0 [69.7–81.1] years, and 448 participants (53.2%) were women. The mean TSH was 6.38± SD 5.7 mIU/L at baseline and decreased at 1 year to 5.66 ± 3.3 mIU/L in the placebo group, compared with 3.66 ± 2.1 mIU/L in the levothyroxine group (p<0.001), at a median dose of 50 μg. Levothyroxine did not significantly change the risk of any of the prespecified cardiovascular outcomes, including cardiovascular events (HR 0.74 [0.41–1.25]), atrial fibrillation (HR 0.69 [0.32–1.52]), or heart failure (0.41 [0.13–1.35]), or all-cause mortality (HR 1.28 [0.54–3.03]), irrespective of history of CVD and age. Conclusion Treatment with levothyroxine did not significantly change the risk of cardiovascular outcomes in older adults with subclinical hypothyroidism, irrespective of a history of cardiovascular disease and age. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT01660126] (TRUST); Netherlands Trial Register: NTR3851 (IEMO80+).